ANALISIS KESALAHAN EJAAN DALAM KARANGAN NARASI PADA SISWA KELAS V SEKOLAH DASAR KECAMATAN SUMEDANG SELATAN - Anggi Citra Apriliana; Avini Martini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to uncover spelling errors (letter use errors, word writing, and punctuation use) of fifth grade students of elementary schools in South Sumedang District, Sumedang Regency. To achieve this goal qualitative descriptive research is carried out with steps: collecting data on students' language errors and conducting language error analysis. The research subjects were fifth grade students of Margacinta Elementary School, Manangga Elementary School, and Pasanggrahan I Elementary School, South Sumedang District. The results of the study showed that there were errors in language in students' narrative essays which included spelling errors (letter usage errors, word writing, and punctuation errors). Spelling errors that often appear are errors in capital letters, incorrect writing of prepositions, errors in the use of punctuation, errors in writing words that are not in accordance with the rules of the correct language, and errors in writing of particles. The largest number of misspellings is Manangga Elementary School with a number of spelling errors of 52 (43.33%) and the smallest number of misspellings, namely Margacinta Elementary School with 27 (22.5%) errors.